Narasi Komunikasi Antarbudaya dalam Film (Studi Pada Film Batas, 2011) - Rafdi Fabian Novrie (CommLine, 2015)
This study aims to determine how the shape of the narrative in the film, and determine the forms of intercultural communication in the film. This research deepens the characters in the film and their functions, so that it becomes a single unit. The framework of this study starts from mass communication, film as mass communication, cultural studies, narrative analysis, and intercultural communication. This study uses narrative analysis as a research method. The data obtained by capturing the scene, and from dialogues that occurred in the film. This film is one of Indonesian films that promote social functions for the community. After the study was conducted, it was found that communication between people, and between cultures must be understood between each other, so as to minimize cultural misunderstandings and establish good communication will make Indonesia better nation, and maintain our own cultural face.